Isolated unilateral brachial plexus injury following carbon monoxide intoxication: a case report and literature review - Liu, Shu; Sun, Houchao; Wang, Shengyuan; Liao, Jincheng; Yang, Xu; Cai, Zhiyou (Frontiers in Neurology, 2024)
Carbon monoxide (CO) is a gas that has no odor or color, making it difficult to detect until exposure leads to coma or death. CO poisoning is one of the most common and deadly poisonings around the world. CO poisoning is a common and often fatal form of poisoning worldwide. A toxic effect of CO is tissue hypoxia, which leads to systemic complications. Additionally, there may be severe neurological symptoms and delayed complications following CO poisoning. However, peripheral neuropathy is relatively rare after CO poisoning. Previously, only one case of unilateral plexopathy after CO poisoning, accompanied by rhabdomyolysis and cognitive dysfunction, has been reported. In this report, an isolated unilateral brachial plexopathy following CO intoxication is described. A key mechanism in this case may be CO-induced spinal cord ischemia. Immediate administration of hyperbaric oxygen therapy (HBOT) is crucial to prevent peripheral neuropathy after acute CO intoxication. Hyperbaric oxygen therapy (HBOT) should be administered immediately after acute CO intoxication to prevent peripheral neuropathy. Additionally, peripheral neuropathy following acute CO intoxication may benefit from consistent rehabilitation training.